Remuneration of Workers in the Perspective of Islamic Law and Current Labor Laws - Arifuddin Muda Harahap; Rika Rahayu; Siti Aisyah Pohan (CV. Rayyan Dwi Bharata, 2023)
The problem of wages is a very important issue that cannot be ruled out, because wages are a source of income that can cover the necessities of life and also wages can affect income, standard of living, community and welfare. However, if workers do not get adequate wages, then this can affect their livelihood and also the purchasing power of workers. This study aims to determine the existing remuneration in Law no. 13 of 2003 concerning Employment in the Perspective of Islamic Law. This study uses qualitative methods using a normative approach. The data sources used are primary legal sources in the form of laws and regulations and secondary data sources in the form of books, journals, the internet. Then, the data is processed and analyzed to produce a scientific research. The amount of wages must be balanced with the work that has been done. Remuneration must also comply with muamalah principles and muamalah principles. These principles cover all forms of muamalah except those specified otherwise in the Al-Qur'an and Hadith, based on voluntary, based on considerations of bringing benefits and avoiding harm, carried out by maintaining justice.